2020
DOI: 10.1038/s41598-020-75683-5
|View full text |Cite
|
Sign up to set email alerts
|

Red-COLA1: a human fibroblast reporter cell line for type I collagen transcription

Abstract: Type I collagen is a key protein of most connective tissue and its up-regulation is required for wound healing but is also involved in fibrosis. Control of expression of this collagen remains poorly understood apart from Transforming Growth Factor beta (TGF-β1)-mediated induction. To generate a sensitive, practical, robust, image-based high-throughput-compatible reporter system, we genetically inserted a short-lived fluorescence reporter downstream of the endogenous type I collagen (COL1A1) promoter in skin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Resident fibroblasts proliferate reactively in response to the microenvironment's external stimulation by secretion of excessive extracellular matrix (ECM) components like collagens. An excessive or prolonged collagen synthesis leads to abnormal scar formation in the skin [ 96 ], fibrotic disorders in cardiovascular and pulmonary diseases [ 97 ], and is associated with poor prognosis in many cancers [ 98 ]. The increase of collagen expression level in response to NMP showed a type I collagen proliferation with fibrosis events and excessive deposition, which was also demonstrated in vivo in aged human-derived cells [ 50 ], and in ovaries [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resident fibroblasts proliferate reactively in response to the microenvironment's external stimulation by secretion of excessive extracellular matrix (ECM) components like collagens. An excessive or prolonged collagen synthesis leads to abnormal scar formation in the skin [ 96 ], fibrotic disorders in cardiovascular and pulmonary diseases [ 97 ], and is associated with poor prognosis in many cancers [ 98 ]. The increase of collagen expression level in response to NMP showed a type I collagen proliferation with fibrosis events and excessive deposition, which was also demonstrated in vivo in aged human-derived cells [ 50 ], and in ovaries [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that the regulation of type 1 collagen in the skin fibroblasts is the underlying mechanism of wrinkle formation in humans. The major factors associated with a decrease in collagen type-1 proteins are UV radiation, chronological ageing, and senescence [23] . Since the COL1A1 and COL1A2 genes are responsible for the production of type-1 collagen, reports have suggested that their transcription is tightly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…We can speculate as to whether the signatures of adaptive collagen-related variation here are the result of historical selection for bone strength related to locomotion, development, and wound repair [ 99 , 100 ]; however, a future step would be first to determine the extent to which these variants represent functional variation. Examples include targeted COL1A1 SNPs in human- and chimpanzee-derived cell lines with RNA-seq, ChIP-seq, and reporter assay technologies to identify the effects of gene expression [ 109 ], as well as investigations of animal models and case–control cohorts that exhibit different BMD profiles [ 16 , 110 ]. As comparative primate functional genomics continues to evolve [ 111 ], we predict that using our study of COL1A1 as a model for other gene-based evolutionary analyses will reveal cryptic variation underlying “disease genes” with potential functional and adaptive significance.…”
Section: Discussionmentioning
confidence: 99%